The Role of the Catholic Church against Changes and Threats to the Value of Work - Kowalik, Dagmara (Religions, 2023)
The purpose of the article is to present the role played by the Catholic Church in Western Europe against civilization’s threats to the value of work in the context of Catholic social teaching. There are historical and contemporary changes and threats to the value of work. The importance of work was analyzed in terms of antiquity, the Middle Ages, during the nineteenth-century industrial revolution and in the era of contemporary IT changes. We present how the value of work was perceived, what role Christianity played and the position of the Catholic Church in relation to social changes and the progress of civilization. It was pointed out how socio-economic transformations and, above all, scientific and technical progress, influenced the threats regarding the personal dimension of work and the subjective role of a man. The evolution of the legal protection of the state against employees and employers, and the position taken by the Catholic Church in this matter were described. It has been shown that old and modern forms of work under the guise of facilities are a threat to the value of work and a human’s subjectivity. The analysis of the positions and documents of Catholic social science allowed us to show a change in the role of the Church, which, from the attitude of real influence in the nineteenth and twentieth centuries, became directed in the 21st century to strengthen active attitudes in the work environment among Catholics. It expects the sensitivity of conscience and open brotherhood, and adopts an attitude of charity and committed action for the benefit of the economically excluded and people deprived of decent work.